2017
DOI: 10.1016/j.mcn.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose γ-secretase inhibition increases secretion of Aβ peptides and intracellular oligomeric Aβ

Abstract: γ-Secretase inhibitors have been considered promising drug candidates against Alzheimer's disease (AD) due to their ability to reduce amyloid-β (Aβ) production. However, clinical trials have been halted due to lack of clinical efficacy and/or side effects. Recent in vitro studies suggest that low doses of γ-secretase inhibitors may instead increase Aβ production. Using a stem cell-derived human model of cortical neurons and low doses of the γ-secretase inhibitor DAPT, the effects on a variety of Aβ peptides we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(52 reference statements)
1
4
0
1
Order By: Relevance
“…Inhibition of γ-secretase using LY411575 decreased secretion of both Aβ40 and Aβ42 equally at all three doses, although the decrease of Aβ42 did not reach statistical significance. The preferential inhibition of Aβ40 over Aβ42 has earlier been shown for other γ-secretase inhibitors, by our group and others [44,45]. This biased inhibition results in an increased Aβ42 to Aβ40 ratio, which is believed to be more amyloidogenic and could be negative for synaptic function [46].…”
Section: Discussionsupporting
confidence: 59%
“…Inhibition of γ-secretase using LY411575 decreased secretion of both Aβ40 and Aβ42 equally at all three doses, although the decrease of Aβ42 did not reach statistical significance. The preferential inhibition of Aβ40 over Aβ42 has earlier been shown for other γ-secretase inhibitors, by our group and others [44,45]. This biased inhibition results in an increased Aβ42 to Aβ40 ratio, which is believed to be more amyloidogenic and could be negative for synaptic function [46].…”
Section: Discussionsupporting
confidence: 59%
“…39 We treated both the HEK293-APPsw and the human iPSC-derived neurons with a very potent GSM, GSM4 (Figure 2C), as reported 40 ; this compound was resynthesized and characterized by us recently. 41 We observed the expected dose-dependent increase in short Aβs (37,38) and decrease in long Aβs (40, 42) (Figure 2D, E). In the HEK293-APPsw cells, GSM4 at as low as 0.29 pM could elevate Aβ37 by 118% but only decrease Aβ42 by 23% (Figure 2D).…”
Section: Aβ37 Production Is More Sensitive To Pharmacological Inhibit...mentioning
confidence: 63%
“…Secreted Aβx‐37, x‐38, x‐40, and x‐42 were quantified in the conditioned media (Figure 2B). We observed the “paradoxical” increase of Aβ generation, especially x‐42, in the 20 nM to 200 nM low dose range of DAPT, an effect reported multiple times with GSIs (eg, 38 ). Further analysis of the pattern of DAPT inhibition showed that Aβ37 was more suppressed by DAPT than Aβ40 or Aβ42, suggesting that Aβ37 production is somewhat more sensitive to the pharmacological action of a γ‐secretase inhibitor.…”
Section: Resultsmentioning
confidence: 81%
“…Surprisingly, recent in vitro studies have found that low doses of GSI may increase Aβ generation. Low doses of DAPT (a GSI) increased the generation of several Aβ peptides, particularly Aβ x– 42 , and increased Aβ oligomers were found in cortical neurons treated with low doses of DAPT ( Agholme et al, 2017 ). Other studies have found rebound effects caused by GSI, such as increased levels of PS1 and other γ-secretase subunits.…”
Section: Molecular Structure-based Amyloid-β Therapeutic Strategymentioning
confidence: 99%